Epidemiological features of hypertension in a high-altitude population in Tibet, China: a cross-sectional study - Yue Yu; Jieru Peng; Zongji Zhaxi; Quzhen Jimei; Heng Shi; Guoxia Bai; Qian Cheng; Chunxia Yang (BMC Public Health)
Abstract Background Hypertension is a significant public health challenge in high-altitude areas of Tibet, China. This study aimed to investigate the current epidemiologic status of hypertension in Tibet and to provide insights for enhancing prevention and control strategies in this population. Methods A cross-sectional study was conducted across seven cities in the Tibet autonomous Region. Using multi-stage stratified cluster sampling, 8,992 residents aged 35–75 were enrolled. Hypertension prevalence, awareness, treatment, control rates, and associated risk factors were analyzed. We conducted descriptive and logistic regression analyses in this study. Results The crude and weighted hypertension prevalence rates were 46.5% and 46.7%, respectively. Stage 2 or higher hypertension accounted for 49.8% of cases. Among hypertensive individuals, 45.2% were aware of their diagnosis, 30.8% received treatment, and only 3.0% achieved blood pressure control. Risk factors included aging, urban residence, alcohol consumption, overweight, obesity, diabetes, and central obesity (all p < 0.05). Monotherapy was used by 94.2% of treated patients, predominantly calcium channel blockers (CCBs). Among CCBs, nifedipine was the most commonly used agent (38.2%), with women more likely to use CCBs and less likely to receive beta-blockers than men (p < 0.05). Conclusions Hypertension in Tibet is characterized by high prevalence, multifactorial risk, and critically low rates of awareness, treatment, and control. Strengthening primary healthcare infrastructure and targeted health promotion programs are urgently needed to address this burden in high-altitude populations.